Intensity Stability Comparison Between Different Colors of Laser Pointer - S., Nurulain; M. A., Zawawi; R. M., Ramli; H., Manap (Penerbit UTHM, 2023)
Different source of light can be used as a main light source in an open path optical method. Sunlight, tungsten lamp, LED, laser, mercury vapor lamp and halogen are the example of the light source. It is important to test the stability of the light source used to avoid inaccuracy in the measurement. The purpose of this project is to determine which color of laser has higher stability. Once the light is switched on, the intensity of the light source changes slowly until it comes to a stable state. Each color has different counts of intensity and stability. Different set of laser pointer is used in this project which included blue, violet, red and green color. An open path optical method is used in the experiment. A different color of laser pointer will be used as a light source while spectrometer will act as a detector. The stability for each color of laser pointer is reported in this paper where the standard deviation for each color is calculated to determined which color have a higher stability. Results shows that standard deviation for green color has the smallest value among these four colors where the standard deviation is15.97.Color with smaller standard deviation has the highest stability.